Spinal load in nurses during emergency lifting of obese patients: preliminary results - Cimolin, Veronica; Cau, Nicola; Tacchini, Elena; Galli, Manuela; Rigoldi, Chiara; Rinolfi, Marco; Aspesi, Valentina; Capodaglio, Edda M; Capodaglio, Paolo (La Medicina del Lavoro, 2016)
Background: Nurses are exposed to the risk of injury while handling patients. This is particularly true for obese patients. Objective: The goal of this paper is to estimate the spinal loads and the related risk of injury to nurses while lifting obese patients from the floor with a bariatric sheet during a hospital emergency. Methods: Six male nurses participated in this study. The biomechanical analysis focused on the lifting strategy. Thirty obese in-patients were enrolled to take part in the experimental study and divided into three groups according to their Body Mass Index (BMI). Three-dimensional motion analysis was conducted using an optoelectronic system. The trunk kinematics and the loading on the spines of the operating nurses were computed. Results: Our data showed that when the nurse was operating from the central handle, his trunk was more flexed at the end of the lift with a reduced range of motion. The values were higher when the nurse lifted patients with higher BMIs. All kinetic parameters and tension in the lumbar muscles at the end of the movement were characterised by lower values for the nurse placed beside the patient’s head or feet if compared to the operator positioned beside the central handle in all patient groups. Conclusions: Our preliminary data suggest that only the reaction load on the spine of the nurse holding the central handle, closest to the patient’s centre of mass, seems to exceed the recommended safety limits.